The right to do sporting event show in the light of new technologies development - Krzysztof Westfal (Kazimierz Wielki University, 2017)
The sporting event, unlike the broadcast from the sports event - which called a videogram, is not subject to copyright protection. Copyright for the videogram, that is the recording, is formed when the work - a recording (videogram) - is being made. There is no legal basis that would establish the right to broadcast sports broadcasts before the broadcast itself is done. Consequently, all and any contracts concerning the sale of sports broadcasting rights have no legal basis for the subject matter of those contracts. The consequences of this legal gap and the risks it brings are particularly evident in the context of technological development and the widespread possibility of recording of a sports events (in whole or in part) using commonly available tools such as a mobile phone by a common viewer. Apart from the issue of compensation for infringement of the stadium regulations, which still remains disputable for imprecise content, the author of the recording (a common viewer equipped with just a mobile phone) is entitled by virtue of the law to own copyrights to the resulting work. The copyrights of the viewer-creator are in conflict with the rights of entities acquiring "broadcasting rights" on the basis of appropriate agreements. Moreover it should be noted that, in business practice, the distribution of sports events broadcasting rights is dealt with by national or international sports organizations, and not by sports facility owners, who distribute tickets for sporting events. As a consequence of the above, the concept of granting the related rights, which subject of which are sporting event, in relation to the so called "Law of the Stadium" as unsatisfactory. The above concept, as well as any other ideas given in the literature of this subject do not offer satisfactory solutions, especially considering the dynamically changing conditions of organizing and broadcasting sports events. Accordingly, as a model of solutions introduced in the legal systems of some foreign countries, it is appropriate to consider the amendment to the Polish Sporting Act and to grant the exclusive right to commercial exploitation of a sporting event to a national sport entity superior over the participants, so the organization responsible for the organization of the sports events. The proposed solution should also provide for a fair redistribution of incomes derived from the commercialization of sporting competition.